Totalitarianism and Colonial Legacy: A Postcolonial Analysis of Muhammad Hanif’s A Case of Exploding Mangoes - Dr. Yasir Arafat (University of Chitral Journal of Linguistics and Literature, 2020)
The current study has taken into consideration Muhammad Hanif’s A Case of Exploding Mangoes (2008). This text is a cut-throat satire on the socio-political history of Pakistan and the interference of military in state affairs. This research highlights the elements of totalitarianism and colonial legacies practiced by General Zia in his dictatorial rule. This research also highlights the failure and inefficiencies of autocratic rule and spotlights the undemocratic ways of such a despotic regimes. The theoretical framework used for this study is taken from Hanna Arendt’s Origin of Totalitarianism (1951) and Frantz Fanon’s The Wretched of the Earth (2004). This study has contextualized the socio-political history of Pakistan discussed in the selected text and highlighted General Zia’s manipulation of people by using Islamization and ideology of nationalism.